Intertextuality in advertising - Kovalchuk, Polina (Taras Shevchenko National University of Kyiv, 2023)
The aim of this research is to study intertextual references that are used in different print and video advertisements; understand why they are used, which linguistic peculiarities they have and what influence they have on the brand’s and product’s perception. The object of this research is print and video advertisements with intertextuality. The subject is the references that are used in these advertisements and their peculiarities. The practical significance of the work is based on the possibility of further usage of it in subjects connected with intertextuality and advertising, as well as for creating effective advertisements with intertextuality on practice. The logic of the research determined the structure of this work: introduction, three chapters, conclusions, bibliography, appendices and summary. The introduction provides general information about this scientific work, including the aim, tasks, relevance, scientific novelty, material, definition of the object and subject, practical significance, methods and structure of the work.
Keywords: Intertextuality; advertising